Cytological Effect of Herbicides on Hexaploid Wheat (Triticum aestivum L.) (Journal of Bio-Science, 2011)
Context: In order to control weeds many chemicals are being used. It is well known that the chromosomal constitution of the cells may be changed as a result of herbicide treatment.Objectives: This investigation was made to study the cytological effects of herbicides on somatic and germ cells of hexaploid wheat. Materials and Methods: Two herbicides namely, Fielder and Ronstar were used with three different concentrations along with control. Treatment duration was 12 hours for each of the concentrations. Seeds of hexaploid wheat were treated and the roots emerged from them were studied for mitotic study. A part of the treated seeds were sown in earthen pots and pollen mother cells along with pollen grain were studied from the plants aroused from these treated seeds. Results: Mitotic index were high as well as low in most of the treatments compared to that of control but did not show any clear relationship based on increasing or decreasing of the doses of herbicides. Interphase chromosome volume was found to decrease in case of Fielder however, increased in case of Ronstar with increasing the concentration of herbicides. Percentage of pollen sterility was found to increase with increasing the concentration of both herbicides. Main chromosomal irregularities were chromosome fragments, bridges, laggards, single and multiple chromatid bridges etc.  Conclusion: Generally it is reported that any chemical might have effect on the plant cells. Mainly investigations have evidenced that the chromosomal anomalies caused by radiation and chemical mutagen is very much common matter now. The herbicides used in the present study showed similar type of radiomimetic effect in the plant cells. Therefore it may be suggested that herbicides should be used in agricultural field maintaining their proper concentration. Key words: Herbicides; Cytological effect; Wheat.DOI: 10.3329/jbs.v17i0.7095J. bio-sci. 17: 21-26, 2009